2022
DOI: 10.1007/s10803-022-05590-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Autistic People and the Criminal Justice System: An Update of King and Murphy (2014)

Abstract: The purpose of this paper was to determine whether recommendations made by King & Murphy (Journal of Autism and Developmental Disorders 44:2717–2733, 2014) in their review of the evidence on autistic people in contact with the criminal justice system (CJS) have been addressed. Research published since 2013 was systematically examined and synthesised. The quality of 47 papers was assessed using the Mixed Methods Appraisal Tool. Findings suggest a limited amount of good quality research has been conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Despite the extensive literature on autism, research exploring autism within the CJS is limited [15,16]. Barriers to completing high-quality research within the CJS include challenges in obtaining detailed developmental histories necessary for a comprehensive assessment, co-occurring conditions and differential diagnoses, and access to clinical populations in secure settings.…”
Section: Autism and The Legal Systemmentioning
confidence: 99%
“…Despite the extensive literature on autism, research exploring autism within the CJS is limited [15,16]. Barriers to completing high-quality research within the CJS include challenges in obtaining detailed developmental histories necessary for a comprehensive assessment, co-occurring conditions and differential diagnoses, and access to clinical populations in secure settings.…”
Section: Autism and The Legal Systemmentioning
confidence: 99%
“…Whilst the link between psychopathy and criminality is well evidenced (11), the relationship between autism and criminality is less clear. Collins et al (12) reported that criminality rates amongst those with autism ranged from 0.2% (13) to 62.8% (14) within their systematic review, indicating an overrepresentation of autism amongst offenders. Despite this, the review suggested that there is little evidence that autistic individuals have an increased risk of committing crimes, highlighting methodological limitations which impacted the reliability of conclusions.…”
Section: Introduction 1autism Psychopathy and Criminalitymentioning
confidence: 99%
“…Article 13 of the Convention on the rights of persons with disabilities ( 10 ) guarantees access to justice in the context of disability as a human right and lays concrete and binding duties on state parties. Most jurisdictions regulate parts of the CJS (i.e., from police proceedings up to convictions and sentencing) for vulnerable defendants like individuals with ASD ( 3 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are more often males, of which many also meet criteria for ADHD, show early life signs of conduct problems, and suffer from substance abuse to a greater extent compared to non-criminal individuals ( 12 , 13 ). Furthermore, offenders with ASD seem to be defined by more co-occurring psychiatric pathology ( 1 ), a delayed diagnosis of ASD ( 2 ), and experiences of victimization and social isolation ( 3 ), compared to individuals with ASD in general. These individuals commit various offenses, but there appears to be a high proportion of violent offenses, particularly arson and sexual offenses ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation